Thirty-Day Readmissions After Endovascular or Surgical Therapy for Critical Limb Ischemia: Analysis of the 2013 to 2014 Nationwide Readmissions Databases. Issue 2 (11th July 2017) - Kolte, Dhaval; Kennedy, Kevin F.; Shishehbor, Mehdi H.; Abbott, J. Dawn; Khera, Sahil; Soukas, Peter; Mamdani, Shafiq T.; Hyder, Omar N.; Drachman, Douglas E.; Aronow, Herbert D.
Abstract : Background: Thirty-day readmission rates have gained increasing importance as a key quality metric. A significant number of patients are hospitalized for the management of critical limb ischemia (CLI), but limited data are available on the incidence, predictors, and causes of 30-day readmission after hospitalization for CLI. Methods: Hospitalizations for a primary diagnosis of CLI during which patients underwent endovascular or surgical therapy (revascularization and/or amputation) and were discharged alive were identified in the 2013 to 2014 Nationwide Readmissions Databases. Incidence, reasons, and costs of 30-day unplanned readmissions were determined. Hierarchical logistic regression models were used to identify independent predictors of 30-day readmissions. Results: We included 60 998 (national estimate, 135 110) index CLI hospitalizations (mean age, 68.9±11.9 years; 40.8% women; 24.6% for rest pain, 37.2% for ulcer, and 38.2% for gangrene). The 30-day readmission rate was 20.4%. Presentation with ulcer or gangrene, age ≥65 years, female sex, large hospital size, teaching hospital status, known coronary artery disease, heart failure, diabetes mellitus, chronic kidney disease, anemia, coagulopathy, obesity, major bleeding, acute myocardial infarction, vascular complications, and sepsis were identified as independent predictors of 30-day readmission. Mode of revascularization was not independently associated with readmissions. Infections (23.5%), persistent or recurrent manifestations of peripheral artery disease (22.2%), cardiac conditions (11.4%), procedural complications (11.0%), and endocrine issues (5.7%) were the most common reasons for readmission. The inflation-adjusted aggregate costs of 30-day readmissions for CLI during the study period were $624 million. Conclusions: Approximately 1 in 5 patients hospitalized for CLI and undergoing revascularization is readmitted within 30 days. Risk of readmission is influenced by CLI presentation, patient demographics, comorbidities, and in-hospital complications, but not by the mode of revascularization. Abstract : Supplemental Digital Content is available in the text.